2020
DOI: 10.1371/journal.pone.0231448
|View full text |Cite
|
Sign up to set email alerts
|

Progression of stroke deficits in patients presenting with mild symptoms: The underlying etiology determines outcome

Abstract: Background and purpose Patients with acute stroke and mild or rapidly improving symptoms frequently show progression. The role of reperfusion treatment in such patients is not clear. We hypothesized that progression was most likely in patients with cortical localization and such patients may benefit from thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Moreover, it is coherent with the previously detailed size issue [33]. Akhtar et al [20] reported the administration of rtPA among RSSI patients as follows: 213 did not receive rtPA, and 45 received it. In Eckert [17], 84 patients were included <3 h and 23 >3 h; rtPA was administered in 51 patients, 30 ≤ 3 h and 11 > 3 h. Interestingly, Rudilosso [23] reported false negatives in 37.5% of treated patients vs 18.8% of not treated patients.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, it is coherent with the previously detailed size issue [33]. Akhtar et al [20] reported the administration of rtPA among RSSI patients as follows: 213 did not receive rtPA, and 45 received it. In Eckert [17], 84 patients were included <3 h and 23 >3 h; rtPA was administered in 51 patients, 30 ≤ 3 h and 11 > 3 h. Interestingly, Rudilosso [23] reported false negatives in 37.5% of treated patients vs 18.8% of not treated patients.…”
Section: Discussionsupporting
confidence: 81%
“…The mean age ranges from 59.8 [6] to 72 years [16], with a women percentage ranging from 32 [14] to 53.1% [6], but with the half of studies ( 7) not reporting the information. In three studies [9,14,17], CTP was performed with a 16 rows scanner; in one study [17], a 40 rows scanner was used; in five studies [6,9,15,16,18], a 128 rows scanner was declared; in two studies [15,21], a 320 rows scanner was used allowing a whole brain perfusion approach and in one study [20] no technical detail was provided. A great variety of postprocessing software was reported, ranging from vendor machines tools [9,[16][17][18][19][23][24][25] to commercially available tools not related to individual vendor machines, such as Vitrea [21,21], RAPID [14], MIStar [15,23], F-STROKE [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation